(3eQhL GdPgH heYGOf GdLhgQs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s ((3eOjfI GdehUd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GHJOY Ndb GdYGde ef ZjQ SGHbI eKGd hHYO agPG GdLRA GdKGdK ef eQhL GdPgH heYGOf GdLhgQ PcQ GdHjhJ GdeYXeI YfO GdjhfGfjjf s
(3BNQgG (B:s
(3jfJgi HPcQ CjGe eYGhjI Hf jRjO Hf eYGhjI heQhGf Hf GdMce hGdeNJGQ Hf CHj YHjO hYHO Gddg Hf GdRHjQ hjJdhg ai GdLRA GdQGHY (B: (3PcQ CjGe YHO Gdedc Hf eQhGf s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs